FROM LIKE TO LEARNING HOW TIKTOK SPARKS EDUCATIONAL ENTHUSIASM - Putri, Salsabila Annisa Suryono; Kuncoro, Anisa Murwaningrum; Arochman, Taufik (Universitas Teknokrat Indonesia, 2024)
This study aims to determine the effect of the TikTok application on the motivation and academic achievement level of Generation Z students in higher education. The data in this study was collected quantitatively with a survey involving 40 students from various semesters in the English study program at Tidar University. The results showed that using TikTok helped students in some ways and harmed them in others. In favourable terms, 54. Seventeen per cent agreed 'strongly' with the proposition that 'TikTok is a source to access relevant and interesting information easily', recognizing the truth of digital communication and content that appeals to Generation Z. Some respondents had a negative attitude towards TikTok. Some respondents had a negative attitude towards TikTok, stating that TikTok can make students lose focus and contribute to procrastination, which is a hot issue in the modern world, namely the problem of time management in the educational framework. This study proves that using TikTok creates a dilemma between risks and possibilities for Generation Z students in educational settings. Considering the advantages and disadvantages of using TikTok in learning and teaching, students and educators should better understand the subject matter and find ways to use TikTok effectively to complement the learning process and simultaneously prevent negative implications. These guidelines are necessary to bring out the instructional facilities of TikTok and prevent the disruption of the learning process.